Using Different Cutoffs to Define Tinnitus and Assess Its Prevalence—A Survey in the Dutch General Population - Rademaker, Maaike M.; Smit, Adriana L.; Brabers, Anne E. M.; de Jong, Judith D.; Stokroos, Robert J.; Stegeman, Inge (Frontiers in Neurology, 2021)
Introduction: Tinnitus prevalence numbers in the literature range between 5 and 43%, depending on the studied population and definition. It is unclear when tinnitus becomes pathologic. Objectives: To assess the tinnitus prevalence in the Dutch general population with different cutoffs for definition. Methods: In this cross-sectional study, a questionnaire was sent to a sample (n = 2,251) of the Nivel (Netherlands Institute for Health Services Research) Dutch Health Care Consumer Panel. Three questions were asked to assess the presence of tinnitus, duration, and frequency of the complaint. We classified people as having pathologic tinnitus when participants experienced it for 5–60 min (daily or almost daily or weekly), or tinnitus for >60 min or continuously (daily or almost daily or weekly or monthly), so tinnitus impact on daily life was measured with the Tinnitus Functional Index (TFI) and a single-item question. Answers were stratified to mid-decade years of age. Prevalence numbers were weighted by gender and age to match the Dutch population. Results: Nine hundred thirty-two of 2,251 participants (41%) filled out the questionnaire. The median age was 67.0 (IQR 17) years. Three hundred thirty-eight of 932 (36%) experienced tinnitus for an undefined amount of time during the last year. Two hundred sixteen of 932 (23%) met our definition of having pathologic tinnitus (21% when weighted for age and gender). The median TFI score for all pathologic tinnitus participants was 16.6 (IQR 21.8). A percentage of 50.4% of the pathologic tinnitus participants had a TFI in the range 0–17, which can be interpreted as not a problem. Conclusion: Twenty-three percent (unweighted) or 21% (weighted) of our sample met our definition of pathologic tinnitus, which was based on a combination of duration and frequency over the last year. The TFI score of 47.7% of the pathologic tinnitus participants is ≥18. This indicates that they consider the tinnitus to be at least “a small problem” [11.1% (unweighted) or 8.9% (weighted) of the total study group]. This study illustrates the difficulties with defining pathologic tinnitus. In addition, it demonstrates that tinnitus prevalence numbers vary with different definitions and, consequently, stresses the importance of using a uniform definition of tinnitus.